miR-15a/16 are upreuglated in the serum of neonatal sepsis patients and inhibit the LPS-induced inflammatory pathway - Wang, Xiaoliang; Wang, Xiaoli; Liu, Xuelian; Wang, Xiaoli; Xu, Jiaju; Hou, Shanshan; Zhang, Xiaohui; Ding, Yanjie (International journal of clinical and experimental medicine, 2015)
Infection in neonates, particular the neonatal sepsis continues to be a global problem with significant morbidity and mortality. The diagnosis of neonatal sepsis is complicated by nonspecific clinical symptomatology, a high-false negative rate, and a delay in obtaining blood culture results. MicroRNAs (miRNAs) have recently been used as finger prints for sepsis, and have been validated to be potential sepsis biomarker recently. In the present study, we investigated the level of several miRNAs, such as miR-15a, miR-16, miR-15b, and miR-223, which have been identified as a biomarker in adult sepsis, in neonatal sepsis patients, and then we analyzed the association of miR-15a/16 with the patient prognosis. Results demonstrated that the level of miR-15a/16 was up-regulated in neonatal sepsis patients than in normal neonatal subjects; however, no statistical difference was disclosed in the miR-15b and miR-223 level between two groups. And the ROC analysis indicated the miR-15a and miR-16 were potent fingerprints for diagnosing neonate sepsis. In order to explore the miR-15a/16 function on the lipopolysaccharide (LPS)-induced inflammatory pathway, the mice macrophage RAW264.7 cells were transiently transfected with miR-15a/16 mimics. And it was demonstrated that the miR-15a/16 transfection down-regulated the Toll-like receptor 4 (TLR4) and Interleukin-1 receptor-associated kinase 1 (IRAK-1) transcription level with a statistical difference in the LPS treated cells. And the suppression capability of miR-15a/16 on the expression of TLR-4 and IRAK-1 were evaluated by western blot. Thus, in present study, we identified miR-15a/16 as potential biomarker for the diagnosis and prognosis of neonatal sepsis, and the upregulated miR-15a/16 downregulated the LPS-induced inflammatory pathway.